Case Report: Maximizing the anti-proteinuric response: a multicenter real-world sparsentan case series in IgA disorders - Ray, Abhisekh Sinha; Errabelli, Praveen; Lathiya, Maulik; Mareedu, Neeharik (Frontiers in Nephrology, 2025)
Immunoglobulin A Nephropathy (IgAN) is a prevalent form of glomerulonephritis that leads to chronic kidney disease (CKD), typically marked by ongoing proteinuria, even when treated with standard therapies such as renin-angiotensin-aldosterone system (RAAS) blockers and occasionally immunosuppression. Proteinuria is a modifiable risk factor crucial for disease advancement. Sparsentan, a dual endothelin receptor and angiotensin receptor blocker (DEARA), has been introduced as a novel therapeutic option focusing on proteinuria. We present a case series featuring seven patients - five diagnosed with IgAN and two with IgA vasculitis (IgAV) - with severe proteinuria who were treated with Sparsentan, sometimes in combination with other medications such as targeted-release formulation (TRF) budesonide, sodium-glucose cotransporter-2 (SGLT2) inhibitors, or mycophenolate. Notable reductions in proteinuria and improvements in blood pressure regulation were observed in these cases. Sparsentan was well-tolerated overall, with no significant hyperkalemia or hepatotoxicity reported in this group. These cases emphasize the real-world experience, promising efficacy and safety of Sparsentan in reducing proteinuria in patients with IgA-mediated glomerular disorders, including its application in combination therapies and patients with concurrent or prior immunosuppression